2022
DOI: 10.2106/jbjs.22.00060
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes and Implant Survivorship of 151 Total Ankle Arthroplasties Using the HINTEGRA Prosthesis

Abstract: Background: Few studies have investigated long-term clinical outcomes of a mobile-bearing total ankle arthroplasty (TAA) system. This study analyzed long-term outcomes of TAA using the HINTEGRA prosthesis at a single, non-developer center.Methods: Primary TAAs were performed on 213 ankles in 194 patients, and 151 consecutive ankles [71%] in 136 patients with a minimum follow-up of 10 years after the primary TAA were included in this study. Clinical results were assessed using a visual analog scale (VAS) pain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Similar to the pain score improvement in this study, multiple TAR studies showed significant postoperative improvement in VAS. 25,26 In terms of range of motion after TAR, Nunley et al 25 showed significant improvements of ankle dorsiflexion (2.9° vs 6.3°) and plantarflexion (22.2° vs 26.9°) in 82 patients who underwent a Scandinavian Total Ankle Replacement (STAR) at an average 61 months follow-up. With respect to ankle motion after an isolated TTR, Taniguchi et al 11 reported on 55 ceramic TTR.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the pain score improvement in this study, multiple TAR studies showed significant postoperative improvement in VAS. 25,26 In terms of range of motion after TAR, Nunley et al 25 showed significant improvements of ankle dorsiflexion (2.9° vs 6.3°) and plantarflexion (22.2° vs 26.9°) in 82 patients who underwent a Scandinavian Total Ankle Replacement (STAR) at an average 61 months follow-up. With respect to ankle motion after an isolated TTR, Taniguchi et al 11 reported on 55 ceramic TTR.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al 12 retrospectively analyzed long-term outcomes of 151 TAAs (136 patients) using the mobile-bearing HINTEGRA prosthesis (Newdeal/Integra). At a minimum follow-up of 10 years, significant improvement was seen in clinical outcome measures and ankle range of motion (p < 0.001).…”
Section: Ankle and Hindfootmentioning
confidence: 99%
“… 1 2 3 4 5 6) However, with complication rates as high as 30%, periprosthetic osteolysis emerges as a significant factor affecting prosthesis longevity. 1 5 7 8) The prevention, diagnosis, and management of osteolysis continue to pose considerable challenges. 9 10) …”
mentioning
confidence: 99%